The importance of soil depth in determining the impacts of mixed plantations with thinning on soil multifunctionality - Guangqiu Cao; Linli Dai; Jingwen Qiu; Tingting Peng; Yongkang Wang; Jiangchun Liu; Carolina Urbina Malo; Yiquan Ye; Qing-Fang Bi (Plant and Soil, 2025)
Background and aims Mixed plantations are known to enhance ecosystem functions compared to monocultures, yet their effects on microbial community, soil organic carbon (SOC) quality, and soil multifunctionality across soil profiles remain unclear. This study explores how mixed plantation combined with thinning influence both above- and belowground litter inputs, and how these affect the dynamics of SOC, microbial activities, and ultimately, soil multifunctionality in subtropical Chinese fir plantations. Methods We analyzed tree growth and litter inputs, active SOC pools, nutrient dynamics, enzyme activities, microbial communities, and soil properties across soil profiles under three management practices: monoculture, thinning, and mixed plantation combined with thinning. Key drivers of active SOC and soil multifunctionality were identified using random forest and structural equation modeling. Results Mixed plantations with thinning enhanced tree productivity and root biomass, reduced litterfall, and promoted active SOC and soil multifunctionality, especially at intermediate soil depths (20–40 cm). These effects were linked to a lower ratio of oxidoreductase to carbohydrase activities and higher microbial diversity. Soil depth emerged as a dominant factor shaping microbial activity and community composition, with its interaction with soil properties significantly influencing active SOC and soil multifunctionality. Structural equation modeling further revealed that active SOC dynamics were strongly correlated with soil multifunctionality across the soil profile. Conclusions Mixed plantations alleviate depth-related constraints on soil processes, improving the microbial roles in promoting active SOC and soil multifunctionality. These findings highlight the potential of mixed plantations to enhance soil health and ecosystem services, particularly in monoculture-dominated systems.